Camille Laurens, Marie Darrieussecq : du « plagiat psychique » à la mise en questions de la démarche autobiographique - Anne Strasser (Contextes)
In fall 2007, Camille Laurens accused Marie Darrieussecq of « physical plagiarism », blaming her for pirating her autobiographical story, Philippe, to write a novel, Tom is Dead. At the heart of these two stories, the death of a child is told from the mother’s point of view. Beyond the similarities noticed by Camille Laurens, the latter denies Marie Darrieussecq the right to tell about the death of a child whereas she had not lived through it herself. This quarrel happened through written work, articles, novels and essays. The study of the arguments given by each party shows that there are several things to question: it is about the genre, the subject and the enunciation. It is a very contemporary quarrel since it shows how blurred genres are, how moralizing literature has become and how suffering has been made sacred in a certain way.